CD200 Receptor Controls Sex-Specific TLR7 Responses to Viral Infection - Karnam, Guruswamy; Rygiel, Tomasz P.; Raaben, Matthijs; Grinwis, Guy C. M.; Coenjaerts, Frank E.; Ressing, Maaike E.; Rottier, Peter J. M.; de Haan, Cornelis A. M.; Meyaard, Linde (PLoS pathogens, 2012)
Immunological checkpoints, such as the inhibitory CD200 receptor (CD200R), play a dual role in balancing the immune system during microbial infection. On the one hand these inhibitory signals prevent excessive immune mediated pathology but on the other hand they may impair clearance of the pathogen. We studied the influence of the inhibitory CD200-CD200R axis on clearance and pathology in two different virus infection models. We find that lack of CD200R signaling strongly enhances type I interferon (IFN) production and viral clearance and improves the outcome of mouse hepatitis corona virus (MHV) infection, particularly in female mice. MHV clearance is known to be dependent on Toll like receptor 7 (TLR7)-mediated type I IFN production and sex differences in TLR7 responses previously have been reported for humans. We therefore hypothesize that CD200R ligation suppresses TLR7 responses and that release of this inhibition enlarges sex differences in TLR7 signaling. This hypothesis is supported by our findings that in vivo administration of synthetic TLR7 ligand leads to enhanced type I IFN production, particularly in female Cd200(-/-) mice and that CD200R ligation inhibits TLR7 signaling in vitro. In influenza A virus infection we show that viral clearance is determined by sex but not by CD200R signaling. However, absence of CD200R in influenza A virus infection results in enhanced lung neutrophil influx and pathology in females. Thus, CD200-CD200R and sex are host factors that together determine the outcome of viral infection. Our data predict a sex bias in both beneficial and pathological immune responses to virus infection upon therapeutic targeting of CD200-CD200R.